Definite and indeterminate nonalcoholic steatohepatitis share similar clinical features and prognosis: A longitudinal study of 1893 biopsy‐proven nonalcoholic fatty liver disease subjects. (7th May 2021) - Ampuero, Javier; Aller, Rocío; Gallego‐Durán, Rocío; Crespo, Javier; Abad, Javier; González‐Rodríguez, Águeda; Gómez‐Camarero, Judith; Caballería, Joan; Lo Iacono, Oreste; Ibañez, Luis; García‐Samaniego, Javier; Martín‐Mateos, Rosa; et al.
Abstract: Background and Aim: Histological score systems may not fully capture the essential nonalcoholic steatohepatitis (NASH) features, which is one of the leading causes of screening failure in clinical trials. We assessed the NASH distribution and its components across the fibrosis stages and their impact on the prognosis and their relationship with the concept of metabolic‐associated fatty liver disease (MAFLD). Methods: Spanish multicenter study including 1893 biopsy‐proven nonalcoholic fatty liver disease (NAFLD) patients from HEPAmet registry. NASH was diagnosed by NAS score ≥4 (including steatosis, ballooning and lobular inflammation) and fibrosis by Kleiner score. The presence of MAFLD was determined. Progression to cirrhosis, first episode of decompensated cirrhosis and death were collected during the follow‐up (4.7 ± 3.8 years). Results: Fibrosis was F 0 34.3% (649/1893), F 1 27% (511/1893), F 2 16.5% (312/1893), F 3 15% (284/1893) and F 4 7.2% (137/1893). NASH diagnosis 51.9% (982/1893), and its individual components (severe steatosis, ballooning and lobular inflammation), increased from F 0 (33.6%) to F 2 (68.6%), and decreased significantly in F 4 patients (51.8%) ( P  = .0001). More than 70% of non‐NASH patients showed some inflammatory activity (ballooning or lobular inflammation), showing a similar MAFLD rate than NASH (96.2% [945/982] vs. 95.2% [535/562]) and significantly higher than nonalcoholic fatty liver (NAFL) subjects (89.1% [311/349]) ( P  < .0001). Progression to cirrhosis was similar between NASH (9.5% [51/539]) and indeterminate NASH (7.9% [25/316]), and higher than steatosis (5% [14/263]) (logRank 8.417; P  = .015). Death and decompensated cirrhosis were similar between these. Conclusions: The prevalence of steatohepatitis decreased in advanced liver disease. However, most of these patients showed some inflammatory activity histologically and had metabolic disturbances. These findings should be considered in clinical trials whose main aim is to prevent cirrhosis progression and complications, liver transplant and death.